(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Background: Hydatid cystic disease is one of the most prevalent zoonosis diseases between people and animals. It develops in several organs, the most significant of which is the liver and lung as a hydatid cyst in numerous hosts, including humans. It causes many complications that may result in death. There are no safe and efficient medicines for this parasite in use, and the research process is ongoing to find such treatments. Materials and Methods: During the period from November 2021 to May 2022, collected 18 samples of hydatid cysts (9 human samples and 9 sheep samples) were examined. DNA isolated from a germinal layer, and amplified of the product using the technique of PCR and sequenced in gene 18S rRNA Internal Transcribed Spacer (ITS1) and (ITS2), which has a molecular weight of (1,100 and 750) base pairs. The studied samples were matched with the samples installed in the gene bank. Results: The results found that there were samples that matched the isolate of the gene bank with different percentages. Human Hydatid Cysts which chosen to draw the evolutionary tree, where the percentage of matching was 99 %. Conclusion: The presence of the parasite was verified by using the genes ITS1 and ITS2 and then drawing the evolutionary tree after matching the studied isolate with the isolate registered in the NCBI and the molecular techniques have significantly improved our comprehension of the variety and distribution of E. granulosus.